(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2015)
Francisco Tamayo Yépez, (Sanare, 1902, Caracas, 1985) is an inescapable reference in the history of Venezuelan naturalistic scientific thinking. His work of educator and as a researcher has as scenery the agrarian Venezuela quickly transformed with the arrival of the oil economy, established on the basis of a despotic State headed by Juan Vicente Gómez. The raw material of his social and ecological thesis is constituted by those transformations of the agrarian country to the country of the mining income; with its consequences on demography, environmental damage, and destruction of ecosystems. The object of this study is to establish the contemporaneousness of Tamayo, highlighting his contributions to a perspective of development within its conservation thought, coming in our interpretation to the theory of sustainability. The analysis of a sample of his writing is realized in order to establish the concepts and categories that identify Tamayo’s thesis referred to the development as a matter of synthesis in the dialectic between man and nature.